Cloning and Expression of Endoglucanase Gene from Thermophilic Bacteria Bacillus sp. RP1 - MAELITA RAMDANI MOEIS; DESSY NATALIA; RAHMA WIDYA NINGRUM; ARI DWIJAYANTI (Microbiology Indonesia, 2014)
An endoglucanase gene from glycoside hydrolase family 5, had been isolated from Bacillus sp. RP1 and cloned into Escherichia coli. The cloned gene comprised the promoter, coding sequence and terminator of the gene.Â  This gene encoded a protein with 499 amino acid residues (Mr=55.2 kDa) with a typical Bacillus signal peptide. The recombinant endoglucanase (EG) had optimum activity at pH 5.0 and 50 Â°C. The recombinant EG was expressed in the extracellular, intracellular, and periplasmic fractions with the highest total activity (60.15%) in the intracellular fraction, measured at three hours after isopropyl-Î²-Dthiogalactopyranoside (IPTG) induction. Three hours after the addition of 1% carboxymethyl cellulose (CMC), there was a two-fold increase in intracellular EG specific activity compared to the uninduced cells. Three hours after the addition of 1 mM IPTG, 1% glucose, 1% galactose or 1% cellobiose the intracellular EG specific activity decreased compared to the uninduced cells.